Using A Cognitive Therapy to Enhance Slow Learners’ Competence: Teacher’s Strategy - Adawiyah, Rabi'atun; Daulay, Sholihatul Hamidah (ENGLISH FRANCA : Academic Journal of English Language and Education, 2022)
The purpose of this study is to look at the capacity of slow learners in elementary school to improve their memory using cognitive therapy. The study was carried out at SDLB Gunung Louser Gayo Lues, the key organizer of inclusion. This study's sample consisted of pupils who are classified as slow learners among children with special needs (slow learners). This study's sample size was 20 students. In qualitative research, data is collected in natural settings and from original sources. More participatory observation (participatory observation), in-depth interviews (in-depth interviews), and recording are used in data collecting procedures. In addition, data collection techniques in qualitative research can also be done by recording data in intensive field notes. Based on the results of data analysis, it was found that there were differences in children's memory abilities before being given therapy with after being given therapy to slow learner children in elementary school. So the hypothesis proposed is that there is a difference in children's memory abilities before being given therapy with after being given therapy to slow learner children in elementary school children.